Left Ventricular Assist Devices - Khuansiri Narajeenron; Wirachin Ying Hoonpongsimanot; Megan Boysen Osborn (eScholarship Publishing, University of California, 2017)
Audience: The audience for this classic team-based learning (cTBL) session is emergency medicine residents, faculty, and students; although this topic is applicable to internal medicine and family medicine residents. Introduction: A left ventricular assist device (LVAD) is a mechanical circulatory support device that can be placed in critically-ill patients who have poor left ventricular function. After LVAD implantation, patients have improved quality of life.1 The number of LVAD patients worldwide continues to rise. Left-ventricular assist device patients may present to the emergency department (ED) with severe, life-threatening conditions. It is essential that emergency physicians have a good understanding of LVADs and their complications. Objectives: Upon completion of this cTBL module, the learner will be able to: 1) Properly assess LVAD patients' circulatory status; 2) appropriately resuscitate LVAD patients; 3) identify common LVAD complications; 4) evaluate and appropriately manage patients with LVAD malfunctions. Method: The method for this didactic session is cTBL.